Validating the Organizational Citizenship Behavior Development Model among Iraqi Secondary School Teachers - Al-Khateeb, Маhа Mohammed Abbas; Emami Rizi, Kobra; Al-Khateeb, Muna Mohammed Abbas; Saeidian Khorasgani, Narges (Iranian Journal of Educational Sociology, 2025)
Purpose: The aim of this study is to validate a model for the development of organizational citizenship behavior (OCB) among Iraqi secondary school teachers.Methods and Materials: This research employed a quantitative approach using a descriptive-analytical design. The research tool was a standardized questionnaire, designed based on the identified dimensions. The validity of the tool was confirmed through Confirmatory Factor Analysis (CFA), and its reliability was verified using Cronbach’s alpha coefficient. The study population consisted of Iraqi secondary school teachers in the 2023-2024 academic year, and the sampling was carried out using a multi-stage cluster sampling method.Findings: The findings indicated that all dimensions of the model, including organizational collaboration, professional development, respect and values, commitment and responsibility, educational innovation, honesty and feedback, well-being and mental health, encouragement of academic growth, and discipline and adherence to principles, were highly valid. The results of the CFA showed acceptable factor loadings (≥0.5), and the Cronbach’s alpha results (≥0.7) indicated adequate reliability of the tool.Conclusion: The current study confirmed that the organizational citizenship behavior development model can be used as a practical tool in educational systems. By emphasizing the dimensions of collaboration, innovation, mental health, and teacher commitment, the model offers a means to improve educational environments and enhance learning quality. The findings may serve as a model for other countries with similar conditions, contributing to the improvement of educational systems.